AKTIVITAS FISIK SISWA SMP PADA ERA PANDEMI COVID-19 - Irfan Kusuma Putra, - (2020)
Aktivitas fisik pada saat pandemi Covid-19 yang berdampak pada pembatasan sosial sangat penting untuk diperhatikan pada siswa-siswa sekolah karena pada usia remaja merupakan awal dari buruk atau tidaknya kesehatan di masa dewasa. Akan tetapi masih banyak remaja yang cukup kurang dalam aktivitas fisik. Oleh karena itu penelitian ini bertujuan untuk menguji apakah terdapat perbedaan aktivitas fisik siswa SMP belajar di rumah dan siswa SMP belajar di sekolah pada era pandemi Covid-19. Sampel laki-laki berjumlah 20 siswa SMP dari 10 siswa SMP belajar di rumah dan 10 siswa SMP belajar di sekolah yang berada di Kabupaten Garut. Instrumen yang digunakan dalam penelitian ini yaiu accelerometer actigraph. Penelitian ini di analisis menggunakan Independent Sampel T Test dengan derajat kebebasan (sig.0.05). hasil dari penelitian ini terdapat perbedaan yang signifikan antara aktivitas fisik siswa SMP belajar di sekolah dan siswa SMP belajar di rumah berdasarkan Average Step Count per day dan MVPA per hour dengan nilai p = 0.043 < 0.05 dan 0,000 < 0,005. Sedangkan aktivitas fisik siswa SMP belajar di sekolah dan siswa SMP belajar di rumah berdasarkan METs per hour tidak terdapat perbedaan yang signifikan. Namun tingkat aktivitas fisik kelompok siswa SMP belajar di sekolah lebih tinggi dari pada siswa SMP belajar di rumah. Hal ini menunjukkan bahwa aktivitas fisik berpengaruh oleh sistem pembelajaran di rumah dan di sekolah. Physical activity during the Covid-19 pandemic which has an impact on social improvement is very important for school students to pay attention to because adolescence is the beginning of bad or bad health in adulthood. However, there are still many teenagers who are lacking in physical activity. Therefore this study aims to test whether there are differences in the physical activity of junior high school students studying at home and junior high school students studying at school during the Covid-19 pandemi era. The male sample consisted of 20 junior high school students from 10 junior high school students studying at home and 10 junior high school students studying at schools located in Garut district. The instrument used in this study was the accelerometer actigraph. This study was analyzed using the Independent Sample T Test with degrees of freedom (sig.0.05). The results of this study, there is a significant difference between the physical activity of junior high school students studying at school and junior high school students studying at home based on the Average Step Count per day and MVPA per hour with a value of p = 0.043. . <0.05 and 0.000 <0.005. Meanwhile, the physical activity of junior high school students who studied at school and junior high school students who studied at home based on MET per hour did not have a significant difference. However, the level of physical activity of a group of junior high school students studying at school is higher than junior high school students who study at home. This shows that physical activity is influenced by the learning system at home and at school.